المصادر اللاوثائقیة للتدوین والتألیف فى العالم الاسلامى :دراسة فى الروایة الشفهیة لدى علماء المسلمین - د. یاسر رجب على (المجلة الدولية لعلوم المكتبات والمعلومات)
The research revolves around the issue of the oral narration of Muslimscientists and the statement of its role as one of the non-documentarysources of codification and authorship in the Islamic world as one of the mainbranches that contributed - besides documentary sources - to intellectual andcultural development in the Arab-Islamic civilization, as well as the close linkbetween the oral novel itself and the codification and composition of Muslimscientists, The objectives of the research were to identify the oral narrative,both in terms of its structure and sources, as well as the factors and aspectsthat influenced it, with its types and sections, and the disclosure of itsconditions and controls, as well as the stages and phases of the oral novel.Theoretical or documentary ; The study was focused on books andliterature for the purpose of extracting the data and facts required of it. Themost prominent results of the study revealed the role of the oral novel in thebeginning of codification and writing in all areas of human knowledge. Shealso stressed the need to be careful in transmitting and writing oral narrativesBooks and books, As well as the disclosure of the controls and conditions setby Muslim scientists to transfer and record oral narratives and ensure theaccuracy and accuracy, as recommended by the study to conduct morehistorical studies that show the role of the rest of the tributaries of otherwriting and writing and the role of writing and writing the Islamic book duringthe Arab Islamic civilization